'Towards a Global Pact for the Environment': International environmental law's factual, technical and (unmentionable) normative gaps. Issue 1 (18th February 2019) - French, Duncan; Kotzé, Louis J.
Abstract : A key feature of the 2018 United Nations (UN) General Assembly Resolution 'Towards a Global Pact for the Environment' is the preparation of a technical and evidence‐based report by the UN Secretary‐General that identifies and assesses possible gaps in international environmental law (IEL) and environment‐related instruments with a view to strengthening their implementation. The gap report will be considered by an ad hoc open‐ended working group to discuss options to address the possible gaps. In this article, we reflect on the likely impact of this initial gap identification and analysis phase of the intergovernmental process. We are specifically concerned with the notion and the nature of 'gaps' in the context of the draft Global Pact, the Resolution and more generally in IEL, and will explore whether the concept of 'gaps' has meaningful value and whether such gaps are factual, technical or normative in nature. While we believe an analysis of the strengths and weaknesses of IEL should be welcomed, we are not entirely convinced, however, that a gap analysis in the form and fashion currently proposed is the most effective or useful way to go about this.